PERFECTION OF THE STATE POLICY IN THE SPHERE OF TOURISM IN THE REPUBLIC OF CRIMEA BY CREATING A SINGLE INFORMATION SPACE - I. Kokhanovskaya (Publishing House of the State University of Management, 2017)
The article is devoted to the problems of improving the state policy in the tourist industry of the Republic of Crimea through the creation of a single information space that is currently at the initial stage of formation, the tactics and strategy of informatization of the tourism industry are determined. The article focuses attention on the fact that the use of modern information and communication technologies will increase the pace of social and economic development of the tourism industry in the Crimea, setting specific tasks for the state authorities of the republic. In conclusion of the published article it is noted that the modern model of information support of the state policy of tourism development should be developed on the basis of the integrated structure of the information management model, where information and public services are organized taking into account the interests of entrepreneurs in the tourism industry and consumer consumers.